Pesticide residues in passifloras crops in regions of high production in colombia (2013)
As one of the most bio-diverse countries in the world, Colombia boasts a wide diversity of highly palatable tropical fruits. Even though Colombian fruit production has primarily targeted the domestic market, several fruit species, such as passion fruit (PassifloraSpp), are steadily gaining ground in the broader international arena.  Production of these crops and respond to raising domestic and international demand, many Colombian small-scale farmers use pesticides for pest and disease control. Inadequate use of pesticides could possibly entail public health risks, environmental contamination and ultimately interfere with international trade. Surveys were carried out to passifloras producers of three spices of passiflora crops, yellow passion fruit, sweet passion fruit and purple passion fruit  from the largest producers municipalities in Colombia with the aim to know the integrate pest control and agricultural practices related with pesticides applied in the crops. Ramdomly sampling was realized and samples were analyzed by multiresidue analysis methodology validated in the laboratory and based on IAEA-QuEChERS method. With the results of survey and laboratory analysis it is showed the presence of pesticide residues that exceed maximum residue limits in some samples and the pesticides identified in the samples correspond to those used by farmers. It was found that the presence of residues is mainly due to the shortcomings in the proper use of agricultural practices related primarily to the implementation of agricultural products no registered for such crops.